Femme, artiste et professeure à la Glasgow School of Art de 1885 à 1914 : une transmission au prisme du genre dans les cours d’arts décoratifs - Sophie Neyret-Tassan (Cahiers Victoriens et Edouardiens)
The Glasgow School of Art was founded in 1845. In 1885, when Francis Newbery became director, the school opened its doors to young girls and developed especially the decorative arts courses. His progressive policy fostered the influence of the GSA in Britain and throughout Europe, and influenced the teaching but also the women’s place in the art world. In order to better understand the stakes of this evolution, it is necessary to identify who were these female professors but also the conditions of transmission and for which audience these courses were intended. Finally, it will be necessary to determine the consequences of this educational opening on the careers of these women.